2022
DOI: 10.1111/acer.14782
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale brain network activation during emotional inhibitory control: Associations with alcohol misuse in college freshmen

Abstract: Background The transition to college is associated with increased risk of alcohol misuse and a consequent increase in negative, alcohol‐related social and health impacts. Traits associated with ongoing brain maturation during this period, including impulsivity in emotional contexts, could contribute to risky alcohol use. Methods This functional magnetic resonance imaging (fMRI) study examined brain network activation strength during an emotional inhibitory control task (Go‐NoGo), which required participants to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…Boys did not show an association between neural response to emotional stimuli and substance use. Cohen-Gilbert et al (2022) N = 60 M age = 18.9 (0.4) 55.5 % Female AUDIT, Counseling Center Assessment of Psychological Symptoms (C- CAPS), Young Adult Alcohol Consequences Questionnaire (YAACQ) Concurrent substance use & effects on neural function Alcohol Emotional Go/No-Go with emotional photos (International Affective Picture System) Negative NoGo > Neutral NoGo Lateral frontoparietal networks (rL- FPN; lL- FPN), dorsal attention network (DAN), salience network (SN) Alcohol use and negative consequences of drinking were negatively associated with DAN recruitment to negative Go trials. This pattern suggests that in young adults with more problematic drinking, negative emotional information interferes more with engagement of neural networks involved in top- down attentional control, compared to those with less alcohol misuse.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boys did not show an association between neural response to emotional stimuli and substance use. Cohen-Gilbert et al (2022) N = 60 M age = 18.9 (0.4) 55.5 % Female AUDIT, Counseling Center Assessment of Psychological Symptoms (C- CAPS), Young Adult Alcohol Consequences Questionnaire (YAACQ) Concurrent substance use & effects on neural function Alcohol Emotional Go/No-Go with emotional photos (International Affective Picture System) Negative NoGo > Neutral NoGo Lateral frontoparietal networks (rL- FPN; lL- FPN), dorsal attention network (DAN), salience network (SN) Alcohol use and negative consequences of drinking were negatively associated with DAN recruitment to negative Go trials. This pattern suggests that in young adults with more problematic drinking, negative emotional information interferes more with engagement of neural networks involved in top- down attentional control, compared to those with less alcohol misuse.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, reduced activity during inhibition with emotionally-charged backgrounds might reflect a failure to regulate emotion, with implications for future self-regulation problems linked to drinking. In a separate study of 60 college freshmen, problematic drinking was linked to less neural recruitment of attention regions during negative emotion No-Go trials, and greater recruitment of frontoparietal regions ( Cohen-Gilbert et al, 2022 ). Other work on response inhibition in 30 adults (mean age 23 years) found that greater binge drinking was associated with reduced neural response in frontal and parietal regions during inhibition against background images of fearful faces ( Herman et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results suggested that greater self-control of adolescents is associated with negative network coupling between the limbic and right fronto-parietal resting state networks ( Rubin et al., 2016 ). However, it has been proven that less involvement of the brain circuitry that supports top-down attentional control predicts more problematic drinking among college students ( Cohen-Gilbert et al., 2022 ). Thus, subjects showed higher levels of IA at a younger baseline time point.…”
Section: Discussionmentioning
confidence: 99%
“…We found MDD patients had significantly increased PC of the FPN and Cere compared with the HC group, suggesting lower intra-modular connections and higher intermodular connections in MDD. The FPN regulates the topdown process of emotion and attention (36). Previous studies frequently reported that atypical connectivity of the FPN was linked to MDD (31,37).…”
Section: Discussionmentioning
confidence: 99%